Advancing Intercultural Understanding and Personal Development Outcomes Through Service-Learning: Insights from an International Student - Neivin M. Shalabi (The University of Alabama, 2022)
Knowledge, experience, and reflection are mutually dependent and interconnected. The things people do comprise their experiences which then become the source of their knowledge. Unless people reflect on their experiences, they are less likely to learn from them (McCarthy, 2003). With this in mind, this essay is a critical reflection account of my experience in a service-learning course I took as a graduate student in a U.S research-based university.